Le débat interprétatif : un genre disciplinaire. Apports et limites d’un « outil » d’analyse de l’évolution d’une discipline scolaire - Dias-Chiaruttini, Ana (Linguarum Arena, 2014)
Based on the elements of a recent research, which focused on the emergence and actual practices of interpretative debate in the teaching of literature, in Cycle 3 primary in school in France, this article is a reflection on the contributions and limitations of the concept of disciplinary genre in school as analysis, both theoretical and methodological, from the evolution of disciplinary contents and teaching practices. It discusses various approaches to this proposed notion within different research teams concepts and outlines the choices that were made and the results build which describe the interpretative debate as a kind of metatextual discourse revealing some discursive learnings, allowing to understand the renewal of the teaching of literature in primary school in France and resistance to renewal.